Distinctive Clinical Profile of Blacks versus Whites Presenting with Sudden Cardiac Arrest - Reinier, Kyndaron (Circulation, 2015)
BACKGROUND: Sudden cardiac arrest (SCA) is a major contributor to mortality, but data are limited among non-whites. Identification of differences in clinical profile based on race may provide opportunities for improved SCA prevention. METHODS AND RESULTS: In the ongoing Oregon Sudden Unexpected Death Study (SUDS), individuals suffering SCA in the Portland, Oregon metropolitan area were identified prospectively. Patient demographics, arrest circumstances, and pre-SCA clinical profile were compared by race, among cases 2002 – 2012 (for clinical history, n = 126 blacks, 1262 whites). Incidence rates were calculated for cases from the burden assessment phase (2002 – 2005; n = 1077). Age-adjusted rates were two-fold higher among black men and women (175 and 90 per 100,000, respectively), compared to white men and women (84 and 40 per 100,000, respectively). Compared to whites, blacks were >6 years younger at the time of SCA and had a higher pre-arrest prevalence of diabetes (52% vs. 33%, p<0.0001), hypertension (77% vs. 65%, p=0.006), and chronic renal insufficiency (34% vs. 19%, p<0.0001). There were no racial differences in previously documented coronary artery disease or left ventricular dysfunction, but blacks had more prevalent congestive heart failure (43% vs. 34%, p=0.04), left ventricular hypertrophy (77% vs. 58%, p=0.02), and a longer QT interval (QTc) (466 ± 36 vs. 453 ± 41, p=0.03). CONCLUSIONS: In this US Community, the burden of SCA was significantly higher in blacks compared to whites. Blacks with SCA had a higher pre-arrest prevalence of risk factors beyond established CAD, providing potential targets for race-specific prevention.